2014
DOI: 10.1007/s00330-014-3388-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the myocardial area at risk using coronary CT angiography and Voronoi algorithm-based myocardial segmentation

Abstract: • Voronoi algorithm allows for three-dimensional myocardial segmentation of coronary CT angiography • Stenosis-related CT myocardial territories correlate to SPECT based area at risk • CT angiography myocardial segmentation may assist in clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 24 publications
0
40
1
Order By: Relevance
“…A recent study has demonstrated the high reprodu-cibility of CTA-based LV myocardial territory and the good correlation of CTbased MAAR with SPECT-based MAAR [10]. SPECT has been established as a clinical standard because of the substantial evidence supporting its use in the diagnosis and management of CAD [5] [20] [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated the high reprodu-cibility of CTA-based LV myocardial territory and the good correlation of CTbased MAAR with SPECT-based MAAR [10]. SPECT has been established as a clinical standard because of the substantial evidence supporting its use in the diagnosis and management of CAD [5] [20] [23].…”
Section: Discussionmentioning
confidence: 99%
“…In diagnostic imaging, a previous study has shown the usefulness of this algorithm for liver segmentation, based on CT portal venography [9], and a recent study has reported that ICA-based stenosis-related CT myocardial territory correlates with the SPECT-based myocardial area at risk (MAAR) [10]. Coronary CTA stenosis-related CT myocardial territory is an assumption of the maximum MAAR that is obtained from a resting coronary CTA dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because there are variations in the myocardial area at risk in each patient, vascular territory misinterpretation on PET corresponding to the culprit or reference vessel can occur. 33 Therefore, quantitative PET and coronary CTA may be complementary for better non-invasive diagnosis.…”
Section: Future Directionsmentioning
confidence: 99%
“…There have been several studies of patient‐specific bull's‐eye maps of the LV 8 , 9 , 10 , 11 . These studies reported patient‐specific mappings between each of the 17 segments and LV territories using CMR, adapting the 17‐segment model using patient‐specific anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies of patient-specific bull's-eye maps of the LV. (8)(9)(10)(11) These studies reported patient-specific mappings between each of the 17 segments and LV territories using CMR, adapting the 17-segment model using patient-specific anatomy. The studies' approach achieved better correspondence between the 17 segments and coronary arterial territories, but could not provide a precise mapping between segments and the AHA recommended nomenclature.…”
mentioning
confidence: 99%